STEREOTIP ETNIS TIONGHOA TERHADAP ETNIS MADURA DI KOTA SURABAYA: STUDI KOMUNIKASI LINTAS BUDAYA - Fariyanti, Riza; Handoko, Rudy; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2015)
Surabaya city has a population of diverse ethnicities and cultures. Cross-cultural communicationis what makes interesting, because the convergence of a culture with other cultures, although there is adifference but still be able to live together. Stereotypes against ethnic, religious and ethnic particular anobstacle in building an effective intercultural communication. The study aims to determine thestereotypical view in cross-cultural communication in the Maduranese ethnic Chinese. To achieve thisgoal, this study uses descriptive qualitative research method with direct observation in the field as well asconducting interviews with respondents of the city of Surabaya native Chinese descent, determinedthrough purposive sampling which determines intentionally respondents using criteria established by theresearchers. The results showed that there is a stereotype in the Maduranese. Stigma Coarse own way,brave fight is still attached to the Maduranese. But there is another stigma that is hardworking, loyaltyand great togetherness.Keywords : Stereotypes, Chinese, Maduranese